ANALISIS METAFORA DALAM LAGU JEPANG BERTEMAKAN BUNUH DIRI - Rilo Pambudi; Alvin Fadhila; Haqi Sang Kautsar; Muhammad Arif Syaifuddin (Jurnal Pendidikan Bahasa Jepang Undiksha, 2021)
This article aims to examine the metaphor that is used in suicidal-themed Japanese songs. This article uses the theory by Stephen Ullman. The data used in this article are from Japanese songs, that is Nautilus by Yorushika, Yoru ni Kakeru by YOASOBI, Inochi ni Kirawareteiru by Kanzaki Iori, Ruru-chan no Jisatsu Haishin by Shinsei Kamattechan, Kuyamu to Kaite Mirai and Umareta Imi Nado Nakatta by Mafumafu, Aka Pen Onegaishimasu by PowaPowaP, and Ikite Itandayona by Aimyon. The data was collected using simak bebas libat cakap (SBLC) method and analyzed using a descriptive method. The purpose of this article is to find out what kind of metaphors are used by songwriters in their lyrics. The results of research conducted on 8 songs found as many as 27 metaphorical data. Out of the 27 data, abstraction metaphors were mostly found with a total of 16 data, followed by anthropomorphic metaphors with a total of 5 data. Abstraction metaphor and synthetic metaphor have 4 data and 2 data respectively.